Broadcasting Licenses: Ownership Rights and the Spectrum Rationalization Challenge - Musey, J. Armand (Science and Technology Law Review, 2012)
This Article examines the showdown between television broadcasters and the government in light of the FCC’s plan to reallocate currently licensed broadcast spectrum to significantly higher value mobile broadband use. The government seeks to do so in an economically, socially and legally efficient manner, and has indicated that it seeks a reallocation process that is voluntary for broadcasters. Nonetheless, any spectrum reallocation proceeding raises the question of whether, and to what extent, television broadcasters ultimately possess rights to licensed spectrum, and what type of compensation, if any, they would be owed if the FCC takes their spectrum licenses involuntarily. This Article finds that broadcasters have a very weak property rights claim over their spectrum licenses. However, broadcasters may be entitled to due process before their licenses can be taken involuntarily; they are almost certainly entitled to seek judicial review of any adverse FCC decisions. Such review would extend the already lengthy FCC rulemaking and adjudication process, and further delay spectrum reassignment. For practical political reasons, including maximizing revenue from future spectrum auctions, the most expedient way to reallocate spectrum is to incentivize the broadcasters to voluntarily participate in a reallocation plan by providing compensation beyond the legally required minimum.